Photoshop CS4 for dummies - Bauer, Peter 1957- (Wiley Pub., 2008)
Describes the basics of Adobe Photoshop CS4, discussing such topics as sizing and resizing images, choosing colors, working with layers, creating composite images, using masks and channels, and adding type.
Print version record
Keywords: Adobe Photoshop; Computer graphics; Photography -- Digital techniques; Infographie; Photographie numérique; computer graphics; COMPUTERS; Computer Graphics; Photography; Digital techniques